2021
DOI: 10.1021/acs.jced.0c00943
|View full text |Cite
|
Sign up to set email alerts
|

Density of n-Heptane + n-Dodecane and Carbon Dioxide + n-Heptane + n-Dodecane Mixtures up to 70 MPa from (293.15 to 363.15) K

Abstract: Density measurements of the n-heptane + n-dodecane binary mixture were performed with a vibrating tube densitometer in the temperature range of (293.15 to 363.15) K and pressure up to 70 MPa at six different n-heptane mole fractions: x 1 = 0, 0.1999, 0.3991, 0.5999, 0.7998, and 1. Densities of the CO2 + n-heptane + n-dodecane ternary mixtures were also measured at the same temperature and pressure ranges for two different isopleths: CO2 (0.4904) + n-heptane (0.2548) + n-dodecane (0.2548), and CO2 (0.7425) + n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…However, for hydrocarbon + CO 2 systems, the DV/V ratio could assume both positive and negative values. The literature shows that positive values are generally observed at pressure typically above 40 MPa [53,54,64,65].…”
Section: Volume Change On Mixing and Excess Volumementioning
confidence: 99%
See 1 more Smart Citation
“…However, for hydrocarbon + CO 2 systems, the DV/V ratio could assume both positive and negative values. The literature shows that positive values are generally observed at pressure typically above 40 MPa [53,54,64,65].…”
Section: Volume Change On Mixing and Excess Volumementioning
confidence: 99%
“…However, the amount of density data available in the literature for more complex rather than binary systems is very scarce. In fact, to the best of our knowledge, only two studies covering the temperature and pressure conditions typically found in offshore reservoirs are available in the literature for ternary mixtures comprising dissolved CO 2 [53,54]. In these studies, the temperature, pressure, and CO 2 mole fraction ranged from (273.15 to 363.15) K, (5 and 100) MPa, and between 0.2 and 0.95, respectively.…”
mentioning
confidence: 99%